In-depth genome and pan-genome analysis of a metal-resistant bacterium Pseudomonas parafulva OS-1 - Kumari, Kiran; Rawat, Vaishnavi; Shadan, Afreen; Sharma, Parva Kumar; Deb, Sushanta; Singh, Rajnish Prakash (Frontiers in Microbiology, 2023)
A metal-resistant bacterium Pseudomonas parafulva OS-1 was isolated from waste-contaminated soil in Ranchi city, India. The isolated strain OS-1 showed the growth at 25-45℃, pH 5.0-9.0, and in the presence of ZnSO4 (0 to 5 mM). Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain OS-1 belonged to the genus Pseudomonas and was most closely related to parafulva species. We sequenced the complete genome of P. parafulva OS-1 using Illumina HiSeq 4000 sequencing platform. The average nucleotide identity (ANI) analysis results indicated the closest similarity to P. parafulva PRS09-11288 and P. parafulva DTSP2. The metabolic potential of P. parafulva OS-1 based on COG, KEGG, and CAZymes indicated high number of genes related to stress protection, metal resistance, multiple drug-efflux etc which is relatively rare in P. parafulva strains. Compared with other parafulva strains, it was found that P. parafulva OS-1 has the unique β-lactam resistance and type VI secretion system (T6SS) gene. Additionally, its genomes encode various CAZymes such as glycoside hydrolases and other genes associated to lignocellulose breakdown, suggesting that strain OS-1 have strong biomass degradation potential.